The effect of respiratory and physical intervention on selected parameters of heart rate variability in hematooncological patients after treatment - Šperková, Martina; Kapounková, Kateřina; Hrnčiříková, Iva; Svobodová, Zora; Malá, Alexandra; Janíková, Andrea; Hadrabová, Markéta (Studia Sportiva, 2020)
The aim of this research was determined the effect of respiratory intervention for twelve weeks and physical intervention for twelve weeks on selected parameters of heart rate variability in hematooncological patients after treatment. Spectral analysis of heart rate variability was measured by DiANS PF8 machine with Medical DiANS PC software. Evaluated were complex indices – Total score and Sympathovagal balance (S-V balance). The intervention programme was composed of three months of respiratory training and then three months of physical training. The experimental group, which absolved this combination of respiratory and physical intervention, was assessed at free time points: firstly, before the respiratory intervention, secondly between the respiratory and the physical intervention and thirdly after the physical intervention. The control group (without intervention) was measured twice between six months. 30 hematooncological patients (16 women and 14 men) were participated in this research, ranging in age 53,74±14,76 years from Internal Hematology and Oncology Clinic of The University Hospital Brno. Results of selected parameters of heart rate variability showed improvements, but without statistically significant effect of intervention programme.
Keywords: hematologické nádory; lymfom; Respiratory System; pohybová aktivita; Physical Therapy Modalities; Breathing Exercises; dýchací soustava; techniky fyzikální terapie; Motor Activity; Exercise Therapy; dechová cvičení; Humans; Lymphoma; lidé; terapie cvičením; Hematologic Neoplasms